Line × tester analysis for combining ability and heterosis in Indian mustard (Brassica juncea) - HS Meena,; Arun Kumar,; Swarnim Kulshrestha,; PD Meena,; Bhagirath Ram,; Anubhuti Sharma,; VV Singh,; Dhiraj Singh, (Journal of Oilseed Brassica, 2026)
Line × tester analysis was carried out to estimate combining ability and heterosis of 18 hybrids developed bycrossing 9 lines with 2 testers of Indian mustard. The F1 hybrids along with parental genotypes planted at theexperimental farm of ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur, India during 2015-16were evaluated for twelve characters, including days to flowering, days to maturity, plant height (cm), numberof primary & secondary branches / plant, main shoot length (cm), number of siliquae on main shoot, siliqualength (cm), number of seeds per siliqua, 1000-seed weight (g), oil content (%) and seed yield (kg/ha).Analysis of variance revealed sufficient genetic variability among parents, hybrids and parent vs. hybrids formost of the traits. The operation of both additive and non-additive gene actions with predominance of nonadditivegene action was observed in controlling seed yield and contributing traits. Estimates of GCA effectsindicated that RH 749, RH 406, Rohini, NRCHB 101 and NPJ 112 were good general combiner. SignificantSCA effects for seed yield, 1000-seed weight, number of seeds/ siliqua and other attributing traits in desirabledirection were recorded in a series of hybrids and a close association between SCA effects and heterosiswas observed amongst the best hybrids identified on the basis of SCA effects. The three hybrids; NRCHB101/ NPJ 112, RH-749/ NPJ 112 and RH-406/ RRN-727 exhibited high magnitude of better parent, standardparent and mid parent heterosis with highly significant SCA effects and higher per se performance for seedyield and important traits. The high yielding cross combinations can be further exploited for improving theseed yield by development superior genotypes and the parents involved in producing heterotic hybrids shall beconverted to well adapted cytoplasmic male sterile or restorer lines.